The Quality of Milk Production in Friesian Holstein (FH) Dairy Cattle Experiencing Repeat Breeding at KUD Tani Wilis Sendang, Tulungagung Regency - Sintya Kumalasari Wibowo; Aldin Akbar Rahmatullah; Cindy Ercha Aulia Putri; Pudji Srianto; Dian Ayu Permatasari; Dadik Raharjo; Rimayanti; Erma Safitri; Mohammad Auzaie Afandi; Nuurin Ajrin Karim (Journal of Applied Veterinary Science And Technology, 2024)
Background: Repeat breeding is a notable reproductive problem where cows do not conceive after several insemination attempts, and it is typically defined as three or more unsuccessful attempts. This results in reduced reproductive efficiency, lower economic sustainability of the dairy farm, and decreased milk quality in dairy cattle.  Purpose: The purpose of this study was to investigate changes in milk quality in Friesian Holstein (FH) dairy cows subjected to repeat breeding at KUD Tani Wilis Sendang, Tulungagung Regency, focusing on the milk’s density, as well as fat, Total Solid (TS), and Solid Non-Fat (SNF) content. Method:  Thirty-two milk samples were collected, including 10 from normal cows for comparison. The samples were analyzed using a Lactoscan to examine the density, fat content, total solid (TS), and solid non-fat (SNF) of milk. The data was subjected to Independent T-Test analysis. Results: The results revealed significant differences (p<0.05) between repeat breeding and normal cow milk samples in terms of specific gravity, fat content, and Total Solids (TS), but not in Solid Non-Fat (SNF). Repeat breeding cow milk exhibited a higher specific gravity (1.0282 vs. 1.0260) but lower fat content (1.08% vs. 4.18%) and Total Solids (9.38% vs. 12.73%) compared to normal cow milk. However, there was no significant difference for Solid Non-Fat (8.36% for repeat breeding vs. 8.55% for normal cows). Conclusion: Repeat breeding cow milk showed increased specific gravity but decreased fat content and Total Solids compared to normal cow milk, while Solid Non-Fat remained relatively consistent.